H13–partially stabilized zirconia nanocomposites fabricated by high-energy mechanical milling and selective laser melting. (15th May 2018) - Deirmina, Faraz; AlMangour, Bandar; Grzesiak, Dariusz; Pellizzari, Massimo
Highlights: SLM processed MMCs based on a hot work tool steel and Partially Stabilized Zirconia (PSZ) with improved microhardness. Increasing the energy density generally enhanced densification. Large amounts of retained austenite in as-built condition for all samples. PSZ particles segregated under all processing conditions but high energy mechanical milling enhances the reinforcement dispersion in the matrix. Limited interfacial reactions between in MMCs. Graphical abstract: Unlabelled Image Abstract: This work demonstrated the feasibility of producing partially stabilized zirconia (PSZ)-reinforced AISI H13 steel composites through mechanical milling (MM) and selective laser melting (SLM). The effects of the energy of MM and SLM energy density on the density, microstructure, phases, and microhardness were investigated. Increasing the energy density (η) generally enhanced densification. However, high energy density and increased thermal stresses led to more spherical pores and thermal microcracks. All samples in the as-built condition showed a large amount of retained austenite (RA), which decreased with decreasing energy density. PSZ particles segregated under all processing conditions due to different densities and thermal conductivities of the matrix and reinforcements. Large, string-like areas of segregated PSZ exhibited cracks and debonding in SLM-processed low-energy MM composite powders, whereas SLM-processed high-energy MM powders exhibited smaller segregated PSZ agglomerates with different morphology; most of the PSZ areas were crack-free and well bonded to the matrix. A limited interfacial reaction layer formed in the H13–PSZ composites. High-energy MM composite powders formed parts with higher relative densities and microhardness than low-energy MM powders. Considerable metastable tetragonal ZrO2 formed in all composites, suggesting the potential transformation toughening effect of PSZ to increase the composite's fracture toughness.